Assembly of cell-laden hydrogel fiber into non-liquefied and liquefied 3D spiral constructs by perfusion-based layer-by-layer technique - Praveen, S. (2015)
In this work, three-dimensional (3D) self-sustaining, spiral-shaped constructs were produced through a combination of ionotropic gelation, to form cell-encapsulated alginate fibers, and a perfusion-based layer-by-layer (LbL) technique. Single fibers were assembled over cylindrical molds by reeling to form spiral shapes, both having different geometries and sizes. An uninterrupted nanometric multilayer coating produced by a perfusion-based LbL technique, using alginate and chitosan, generated stable 3D spiral-shaped macrostructures by gripping and affixing the threads together without using any crosslinking/binding agent. The chelation process altered the internal microenvironment of the 3D construct from the solid to the liquefied state while preserving the external geometry. L929 cell viability by MTS and dsDNA quantification favor liquefied 3D constructs more than nonliquefied ones. The proposed technique setup helps us to generate complex polyelectrolyte-based 3D constructs for tissue engineering applications and organ printing.